2005
DOI: 10.1007/s11103-005-8880-2
|View full text |Cite
|
Sign up to set email alerts
|

Photoregulation of the Greening Process of Wheat Seedlings Grown in Red Light*

Abstract: Wheat seedling grown with their shoot bottom exposed to red light (400 micromol m(-2) s(-1)) either with constant illumination or light-dark cycles did not accumulate chlorophyll. This near-etiolation response was manifested by a critical threshold intensity of red light and did not need continuous illumination. The inhibition of the greening process resulted from reduced synthesis of glutamate-1-semialdehyde and consequent reduction in tetrapyrrole precursor 5-aminolevulinic acid. Red light perceived by the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 60 publications
(60 reference statements)
3
48
0
Order By: Relevance
“…Chl reduction was observed under red light as a result of a decrease in aminolevulinic acid (Tanaka et al, 1998;Sood et al, 2005), PPIX, MGPP, and Pchlide (Fan et al, 2013). In our study, porphyrin levels were not reduced by red light (Fig.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Chl reduction was observed under red light as a result of a decrease in aminolevulinic acid (Tanaka et al, 1998;Sood et al, 2005), PPIX, MGPP, and Pchlide (Fan et al, 2013). In our study, porphyrin levels were not reduced by red light (Fig.…”
Section: Discussionsupporting
confidence: 43%
“…Blue light induces higher Chl a/b ratios (Rivkin, 1989;Demarsac et al, 1993;Chen et al, 2014;Hoffmann et al, 2015) and greater accumulations of Chl (Kurilčik et al, 2008;Poudel et al, 2008;Hoffmann et al, 2016). Red light inhibits Chl synthesis at lower concentrations of Chl and precursors like 5-aminolevulinic acid (Tanaka et al, 1998;Sood et al, 2005), protoporphyrin IX (PPIX), magnesium protoporphyrin IX (MGPP), and protochlorophyllide (Pchlide) (Fan et al, 2013). Moreover, the mole percentages of PPIX, MGPP, and Pchlide also respond to various physiological conditions and genotypes Hsu et al, 2011;Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the effect of light quality on the chlorophyll a/b ratio in cucumber leaves (Hogewoning et al, 2010b). Several studies suggested that red light inhibited the formation of chlorophyll because 5-aminolevulinic acid, a biosynthetic precursor to chlorophyll, was reduced under red light (Tanaka et al, 1998;Sood et al, 2005). Blue light was reported to play a crucial role in the formation and accumulation of chlorophylls (Dougher and Bugbee, 1997;Li et al, 2012;Fan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have shown rice and wheat seedling grown with their shoot bottom exposed to constant red light or when given in the form of light-dark cycles do not accumulate chlorophyll (Chl) (Gupta et al 2010;Roy et al 2013;Sood et al 2005;Sood et al 2004;Tripathy and Brown 1995). Red light perceived by the shoot bottom downregulates the protein and gene expression of the enzymes involved in the biosynthesis of tetrapyrroles (Sood et al 2005;Sood et al 2004;Tripathy and Brown 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Red light perceived by the shoot bottom downregulates the protein and gene expression of the enzymes involved in the biosynthesis of tetrapyrroles (Sood et al 2005;Sood et al 2004;Tripathy and Brown 1995). This red-light-induced suppression of photomorphogenesis is a red high-irradiance response (red HIR) of PhyA (Roy et al 2013).…”
Section: Introductionmentioning
confidence: 99%